Pengaruh Pengetahuan Bidang Otomotif Terhadap Minat Beralik ke Kendaraan Sepeda Motor Hybrid - Arif Wahyudiono; Azamataufiq Budiprasojo; Yuana Susmiati (Jurnal Teknik Terapan, 2026)
This study aims to analyze the effect of automotive knowledge on public interest in switching to hybrid motorcycles. The research is motivated by the growing need for low-emission vehicles and the importance of consumer understanding in the adoption of hybrid technology. A quantitative research method was employed by distributing questionnaires to 100 respondents using an incidental sampling technique. The research instrument was tested for validity and reliability, and the collected data were analyzed using normality tests, homogeneity tests, Spearman Rank correlation, and the Mann–Whitney U-Test. The results indicate a strong and significant relationship between automotive knowledge and interest in hybrid motorcycles (ρ = 0.761; Sig. = 0.000). However, no significant difference in interest was found between respondents with high and low levels of automotive knowledge (Sig. = 0.554). Thus, automotive knowledge does not have a significant effect on public interest. These findings suggest that the decision to adopt hybrid vehicles is influenced more strongly by other factors, such as perceived usefulness, affordability, and infrastructure readiness.